Optimization of a milk pregnancy-associated glycoprotein enzyme-linked immunosorbent assay test for pregnancy in Holstein cows using time-dependent cut-points between 23 and 90 days after insemination - J. Durocher; R.K. Moore; E. Molgat; S.J. LeBlanc; S. Dufour (Journal of Dairy Science)
ABSTRACT: Our hypothesis was that the accuracy of a commercial milk pregnancy-associated glycoprotein (PAG) ELISA test using the same thresholds at all stages of gestation would be improved by adjusting the cut-points according to the number of days since last breeding (DSLB) between 23 and 90 d after insemination in Holstein dairy cows. Our objectives were to develop a DSLB-specific set of thresholds that would provide better test performance under field conditions and provide more information for the inconclusive test results, by dichotomizing these into “probably open” and “probably pregnant” categories. Milk samples (n = 182,738) submitted to the Lactanet (Canadian Dairy Herd Improvement) laboratory from 2013 to 2021 for pregnancy testing using a commercial PAG ELISA test were compared with records on insemination outcomes. The data were separated randomly into a training dataset used to develop the DSLB-specific interpretation grid and a validation dataset to quantify its test characteristics and compare the performance of the DSLB-specific and fixed thresholds. Our aim was to achieve negative predictive value >0.99 at all stages of test use and positive predictive value (PPV) ≥0.95 at ≤59 d and ≥0.99 between 60 and 90 d after insemination. Neither approach met these targets between 23 and 25 DSLB. The DSLB-specific interpretation grid had greater PPV than the fixed threshold between 26 and 49 DSLB and met the targets. Both approaches were very near the targets of performance between 50 and 90 DSLB. The DSLB-specific interpretation grid has a similar prevalence of inconclusive test results compared with the fixed threshold but provided additional information on the likelihood of the cow being pregnant or open. Classification of milk PAG results using DSLB-specific cut-points improved the predictive value of pregnancy diagnosis between 23 and 49 d after insemination.